(3eOjQ GdeOQSI GdQSejI aj bVGAj GdeJf hcSQhGf(B:(3GNJjGQg,GYOGOg, eSDDdjGJg(B-(3Hjf GdfU hGdhGbYs - (3agO, YHOh GdNhQj CfWhGfs ((3HjQhJs (3GdLGeYI GddHfGfjI (B- (3cdjI GdJQHjI, GdYeGOIs, 2002)
(3jJdNU GdgOa GdYGe dgPg GdOQGSI HGdJYQa Ydi GdCSS hGdeYGjjQ GdJj jJe HehLHgG GNJjGQ hEYOGO hJYjjf GdeOjQjf aj GdeOGQS GdQSeSI GddHfGfjI hJMOjO GdeSDhdjGJ NdGd eeGQSJge dhXjaJge(B. (3CeG GdCgOGa GdNGUI agj cGdJGdj(B: 1) (3JMOjO hGbY eOjQj GdeOGQS GdQSeSI hGdeTcdGJ GdJj jYGfhf efgG(B. 2) (3GdJYQa Edi Cge eYGjjQ hCSGdjH GNJjGQ eOjQj GdeOGQS(B. 3) (3GdJYQa Edi CSGdjH GNJjGQ eOjQj GdeOGQS GdQSejI GddHfGfjI(B. 4) (3EHQGR GdJaGhJ Ch GdJLGfS Hjf EecGfjGJ GdeOjQ hGdegeGJ GdehcdI dg(B. 5) (3EbJQGM ELQGAGJ dYedjI GNJjGQ eOjQj GdeOGQS(B. (3EYJeOJ GdOQGSI Ydi GdefgL GdhUaj GdPj jOQS hGbY eOjQj GdeOGQS GdQSejI hgh jfbSe Edi Tbjf fXQj hYedj(B. (3GSJfOJ GdOQGSI Edi ebGHdGJ eY YjfI ef eOjQj eOGQS QSejI aj bVGAj GdeJf hcSQhGf JHdZ fSHJgG (B20% (25 (3eOQSI ef CUd (B125). (3CeG COhGJ GdOQGSI abO TedJ GSJHjGfkG ehLgkG Edi eOjQj GdeOGQS JeMhQJ GdCSFdI ajg Mhd GdCSS hGdeYGjjQ GdeJHYI aj JYjjf GdeOjQ hCHQR GdeTcdGJ GdJj JYJQVg aj GdeOQSI(B. (3JHjf ef NdGd gPg GdOQGSI eG jdj(B: 1) (3Cf hGbY JYjjf hGNJjGQ GdeOjQjf aj GdeOGQS GdQSejI aj bVGAj GdeJf hcSQhGf dG jSJfO Edi GYJHGQGJ afjI hJQHhjI aj CZdH GdCMjGf, hCf dG CSGdjH hdG eYGjjQ eYjfI aj gPG GdJYjjf(B. 2) (3Cf GdeOjQ djS EdG MGaX fXGe agh jeGQS GdegGe GdJj jWdH efg GdJaJjT GdbjGe HgG CeG HGbj GdegGe agh ebqUQ ajgG CMjGfG cKjQI hjYRh YOe eeGQSJgG JGQI Edi YOe hLhO GdUdGMjGJ Ch GdEecGfGJ GdeGOjI hWhQG Edi YOe EYOGOg Ch EJbGfg dgG(B. 3) (3Ef GdeeGQSjf dHYV GdegGe CcKQ ef ZjQge ge CUMGH GdTgGOGJ GdYGdjI hNUhUG GdcaGAI aj GdJQHjI Ke GdELGRI(B. 4) (3Ef GdfSGA GdeOjQGJ jeGQSf egfJgf HWQjbI CfLM hHYWGA CcHQ ef GdQLGd GdeOQGA(B. 5) (3Cf SfhGJ GdNHQI YfO GdeOjQ JLYdg eJecfG ef Yedg (B. 6) (3Cf GdYdGbI Hjf GdeLJeY GdeMdj hEOGQI GdeOQSI gj Cbhi aj GdbQjI eeG Ydjg aj GdeOjfI(B.s
(3GdfhY (B: (3QSGdIs
Keywords: (3GdGOGQI GdeOQSjIs; Gestion scolaire; Maten et Keserouane; Maten et Keserouane; Public Sector; School management; Secteur Public; (3GdJYdje GdQSejs; (3GdeJf hcSQhGfs